2016
DOI: 10.1016/j.toxrep.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Does amikacin treatment cause subclinical hearing loss in patients with cystic fibrosis?

Abstract: IntroductionAminoglycosides (AGs) have been widely used for potential life-threatening bacterial infections. Although AGs are well known for their ototoxic side effects, some AGs such as amikacin are considered less harmful to auditory functions; thus, auditory monitoring is mostly neglected during treatment with these drugs.ObjectiveTo reflect the potential auditory hazards of repeated amikacin use on the patients with cystic fibrosis (CF).Method32CF patients with prior exposure to at least 3 courses of amika… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…This study showed a very high rate of hearing loss in both the standard (38%) and extended high frequency region (47%) for children, teens and young adults with CF who have received IV-AG antibiotics to treat lung exacerbations. Estimates of hearing loss vary in part due to the criterion for normal-hearing; our study included slight hearing loss (>15 dB HL) in either the SF or EHF range, so the estimates are higher than studies that have used more conservative criteria (e.g., Stavroulaki et al, 2002; Solmaz et al, 2016). Using hearing loss criteria similar to the current study, (2011)Al-Malky et al reported clinically normal hearing (0 to 15 dB HL) from 0.25 to 12.5 kHz in children with CF (n = 45) and little to no previous exposure to IV-AGs (≤ 5 courses).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed a very high rate of hearing loss in both the standard (38%) and extended high frequency region (47%) for children, teens and young adults with CF who have received IV-AG antibiotics to treat lung exacerbations. Estimates of hearing loss vary in part due to the criterion for normal-hearing; our study included slight hearing loss (>15 dB HL) in either the SF or EHF range, so the estimates are higher than studies that have used more conservative criteria (e.g., Stavroulaki et al, 2002; Solmaz et al, 2016). Using hearing loss criteria similar to the current study, (2011)Al-Malky et al reported clinically normal hearing (0 to 15 dB HL) from 0.25 to 12.5 kHz in children with CF (n = 45) and little to no previous exposure to IV-AGs (≤ 5 courses).…”
Section: Discussionmentioning
confidence: 99%
“…For example , Stavroulaki et al (2002) reported normal thresholds (≤ 20 dB HL) from 0.25 to 8 kHz in a pediatric CF cohort with a history of gentamicin exposure (n = 12; range = 5.2 to 14.1 yr.) at baseline and following gentamicin treatment (4mg/kg/day; mean = 14 days; range = 11 to 29). Solmaz et al (2016) reported 12% of individuals with CF (mean = 8.3 yr.; range = 5 to 13) with more than 3 courses of IV amikacin had hearing loss when using a pure-tone average (0.5, 1, 2, and 4 kHz) greater than 25 dB HL. However, when the hearing loss threshold was decreased to > 15 dB HL, 80% of ears in the CF group had hearing loss.…”
Section: Prevalence Of Hearing Lossmentioning
confidence: 99%